STAR splicing mutations cause the severe phenotype of lipoid congenital adrenal hyperplasia: insights from a novel splice mutation and review of reported cases. (17th August 2013) - Camats, Núria; Pandey, Amit V.; Fernández‐Cancio, Mónica; Fernández, Juan M.; Ortega, Ana M.; Udhane, Sameer; Andaluz, Pilar; Audí, Laura; Flück, Christa E.
Summary Objective The steroidogenic acute regulatory protein (StAR) transports cholesterol to the mitochondria for steroidogenesis. Loss of StAR function causes lipoid congenital adrenal hyperplasia (LCAH) which is characterized by impaired synthesis of adrenal and gonadal steroids causing adrenal insufficiency, 46, XY disorder of sex development (DSD) and failure of pubertal development. Partial loss of StAR activity may cause adrenal insufficiency only. Patient A newborn girl was admitted for mild dehydration, hyponatremia, hyperkalemia and hypoglycaemia and had normal external female genitalia without hyperpigmentation. Plasma cortisol, 17OH‐progesterone, DHEA‐S, androstendione and aldosterone were low, while ACTH and plasma renin activity were elevated, consistent with the diagnosis of primary adrenal insufficiency. Imaging showed normal adrenals, and cytogenetics revealed a 46, XX karyotype. She was treated with fluids, hydrocortisone and fludrocortisone. Design, Methods and Results Genetic studies revealed a novel homozygous STAR mutation in the 3′ acceptor splice site of intron 4, c.466‐1G>A (IVS4‐1G>A). To test whether this mutation would affect splicing, we performed a minigene experiment with a plasmid construct containing wild‐type or mutant StAR gDNA of exons–introns 4–6 in COS‐1 cells. The splicing was assessed on total RNA using RT‐PCR for STAR cDNAs. The mutant STAR minigene skipped exon 5 completely and changed the reading frame. Thus, it is predicted to produce an aberrant and shorter protein (p.V156GfsX19). Computational analysis revealed that this mutant protein lacks wild‐type exons 5–7 which are essential for StAR‐cholesterol interaction. Conclusions STAR c.466‐1A skips exon 5 and causes a dramatic change in the C‐terminal sequence of the protein, which is essential for StAR–cholesterol interaction. This splicing mutation is a loss‐of‐function mutation explaining the severe phenotype of our patient. Thus far, all reported splicing mutations of STAR cause a severe impairment of protein function and phenotype.